A comparative investigation of low work‐function metal implantation in the oxide region for improving electrostatic characteristics of charge plasma TFET. (6th February 2019) - Aslam, Mohd.; Sharma, Dheeraj; Yadav, Shivendra; Soni, Deepak; Sharma, Neeraj; Gedam, Anju
Abstract : Abruptness at tunnelling junction is a vital issue with doped tunnel field‐effect transistor (TFET) to achieve improved electrostatic characteristics. This task is more problematic for charge plasma TFET (CP‐TFET) because of large tunnelling barrier at the channel/source interface. In this regard, an effective approach has already been employed through implantation of a horizontal metallic splint (HMS) inside the dielectric region near channel/source joint for improved electrical behaviour of CP‐TFET. However, placement of a vertical metal splint (VMS) provides contact for HMS and gate electrode, which gives magnificent analogue/DC characteristics for newer structure. Combination of HMS and VMS (i.e. double metal splint (DMS)) increases electron density at channel/source junction for improved electron tunnelling rate compared with only HMS structure. In this regard, a complete comparative analysis of DMS CP TFET (DMS‐CP‐TFET) is performed between CP‐TFET and HMS‐CP‐TFET. Furthermore, consequence of length and work‐function variation of DMS and HMS on DC/RF parameters is investigated in device optimisation part of this work.